IMPROVING STUDENTS’ FACTUAL REPORT WRITING SKILL BY USING CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) METHOD - Yadi Kusmayadi; Yayan Suryana (Indonesian EFL Journal, 2017)
Content and Language Integrated Learning (CLIL) seems worthy to investigate since it applies a language other than the student’s mother tongue used as a medium of instruction. In this research, the researcher aims to portray two objectives, namely identifying whether CLIL method is effective to improve students’ factual report writing skill, and examining students’ attitude towards the implementation of this method. This research employs a quasi-experimental design through applying two instruments, namely tests which consists pre-test and post-test, and questionnaires. 60 students of eleventh-grade social class of a state senior high school in Kuningan are involved in the research. They are divided into a control and an experimental group. Tests are analysed quantitatively to identify the first research objective, questionnaires are analysed with descriptive statistic to examine the second research objective. The result taken from independent t-test shows that there is a significant difference on the students’ writing skill since the level of significant is lower than the alpha (0.0000.005) which indicates that CLIL is effective in improving students’ writing skill. Furthermore, the result taken from questionnaires portrays that students show positive attitude towards the implementation of CLIL in teaching and learning process.Keywords: Content and Language Integrated Learning (CLIL), factual report, writing skill